2018
DOI: 10.3389/fmicb.2018.01107
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Tests Using Culture, Xpert MTB/RIF, and SAT-TB in Sputum Plus Bronchial Alveolar Lavage Fluid Significantly Increase Diagnostic Performance of Smear-Negative Pulmonary Tuberculosis

Abstract: At present, tuberculosis remains a serious threat to human health. The diagnosis of pulmonary tuberculosis (PTB) is still difficult, and the prominent challenge for diagnosis is the lack of a highly sensitive and specific method. In order to explore the diagnostic value of parallel tests, this study prospectively enrolled 258 patients with smear-negative PTB from May 2, 2015 to December 31, 2016. The sputum specimens and bronchial alveolar lavage fluid (BALF) samples from all patients were assessed for MTB det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Though the application of TB DNA detection considerably raises the detection rate of PTB, DNA as an amplified product can easily spark laboratory cross-contamination and cause false-positive results, thereby leading to errors of clinical diagnosis. Another one uses RNA as a template, with the target RNA amplified by PCR to detect RNA products of M. tuberculosis in specimens [ 8 ]. During this approach, RNA is the initial target, and gene contamination can be effectively avoided owing to the fact that RNA is extremely easily degradable, which supports that RNA only exists in live bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the application of TB DNA detection considerably raises the detection rate of PTB, DNA as an amplified product can easily spark laboratory cross-contamination and cause false-positive results, thereby leading to errors of clinical diagnosis. Another one uses RNA as a template, with the target RNA amplified by PCR to detect RNA products of M. tuberculosis in specimens [ 8 ]. During this approach, RNA is the initial target, and gene contamination can be effectively avoided owing to the fact that RNA is extremely easily degradable, which supports that RNA only exists in live bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicated that the specificity of SAT-TB for the diagnosis of PTB is almost 100%, with the sensitivity and accuracy reaching 75.8% and 80.2%, respectively [ 7 ], suggesting that SAT-TB as a new detecting method has potential clinical value in PTB diagnosis. Another advantage of SAT-TB is that it targets RNA rather than DNA, and hence, it is capable of detecting live bacteria [ 8 ]. This paper was designed to compare the SAT-TB detection technique combined with acid-fast staining with the MGIT 960 culture test and analyze the sensitivity as well as the specificity of SAT-TB or SAT-TB combined with acid-fast staining for PTB diagnosis so as to evaluate their application value in the diagnosis and treatment of PTB.…”
Section: Introductionmentioning
confidence: 99%
“…Tuberculosis has become the world's second leading cause of death due to infectious disease after AIDS. 14,15 However, in most parts of Asia, Africa, and Russia, the situation of prevention and control of tuberculosis is not very satisfactory due to the eco- Human heterogeneous nuclear ribonucleoproteins A2/B1 (3.94%). 17 In addition to common tuberculosis, the incidence of extrapulmonary tuberculosis is also increasing.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity and specificity of SAT to diagnose TB were 96 and 88%, respectively (20). SAT of sputum and bronchial alveolar lavage fluid significantly increases the diagnostic performance of smearnegative and sputum-scare pulmonary TB in our hospital (10,21). Thus, in this study, we aimed to use EBUS-TBNA biopsy specimens to validate and test the performance of the SAT-TB to differentially diagnose sputum-negative TB from sarcoidosis.…”
Section: Introductionmentioning
confidence: 98%